Plasmodium vivax myocarditis in a child - Patra DCH, MD1, Syed Sadat Ali MD2*, P.A. Balaji MD2, Syed Ahmed Mustafa DCH, (DNB) 1, Vikram (International Multidisciplinary Research Journal, 2011)
We report the first documented case of myocarditis associated with Plasmodium vivax malaria in a child who presented with features of cerebral malaria. Clinical features of shock developing in a patient of severe Plasmodium vivax malaria, especially with stable haematocrit, should be investigated by electrocardiogram and/ or cardiac enzymes and echocardiogarphy to rule out myocarditis.